Potential application of the probiotic Bacillus licheniformis as an adjuvant in the treatment of diseases in humans and animals: A systematic review - Ramirez-Olea, Hugo; Reyes-Ballesteros, Bernardo; Chavez-Santoscoy, Rocio Alejandra (Frontiers in Microbiology, 2022)
The use of Bacillus licheniformis as a probiotic has increased significantly in recent years. Published reports demonstrate that it provides multiple benefits for health. Although there are already studies in humans and is marketed, it is mostly used in the veterinary industry still. However, its benefits could be extrapolated to humans in the future. This review addresses the application of B. licheniformis, its sporulation, mechanisms of action, and its role in the resolution, treatment, and prevention of different conditions and diseases. It focuses on scientific advances from 2016 to mid-2022 and emphasizes on the most common diseases in the general population. Most of the 70% of published studies about the health benefits of B. licheniformis have been published from 2016 until now. Modulation of gut microbiota, antimicrobial activity, growth promoter, anti-inflammatory and immunostimulatory effects, aid in lipid profile regulation, increase in neurotransmitters, and stress reduction, among other mechanisms of action, were identified in Bacillus licheniformis. These results provide novel possible applications of this and other probiotics in general. Although many benefits can be reported on a microorganism, the combination with others could provide a better effect. Further studies like this need to be done to understand the specific advantages of each probiotic and its strains and therefore achieve a better selection of them for a specific disease or disorder.